Is blended learning and problem-based learning course design suited to develop future public health leaders? An explorative European study - Karen D. Könings; Nynke de Jong; Christa Lohrmann; Linas Sumskas; Tony Smith; Stephen J. O'Connor; Ingrid A. E. Spanjers; Jeroen J. G. Van Merriënboer; Katarzyna Czabanowska (Frontiers Media S.A., 2018)
Abstract Background Public health leaders are confronted with complex problems, and developing effective leadership competencies is essential. The teaching of leadership is still not common in public health training programs around the world. A reconceptualization of professional training is needed and can benefit from innovative educational approaches. Our aim was to explore learners' perceptions of the effectiveness and appeal of a public health leadership course using problem-based, blended learning methods that used virtual learning environment technologies. Case presentation In this cross-sectional evaluative study, the Self-Assessment Instrument of Competencies for Public Health Leaders was administered before and after an online, blended-learning, problem-based (PBL) leadership course. An evaluation questionnaire was also used to measure perceptions of blended learning, problem-based learning, and tutor functioning among 19 public health professionals from The Netherlands (n = 8), Lithuania (n = 5), and Austria (n = 6). Participants showed overall satisfaction and knowledge gains related to public health leadership competencies in six of eight measured areas, especially Political Leadership and Systems Thinking. Some perceptions of blended learning and PBL varied between the institutions. This might have been caused by lack of experience of the educational approaches, differing professional backgrounds, inexperience of communicating in the online setting, and different expectations towards the course. Conclusions Blended, problem-based learning might be an effective way to develop leadership competencies among public health professionals in international and interdisciplinary context.